Exploring The Skirmish And Tragic Encounters In Thomas Hardy’s Tess Of The D’urbervilles - Dr. Hassan Bin Zubair (Corresponding Author) , Anum Saeed , Dur-e-Afshan Babar (Migration Letters, 2024)
This research explores the tragic elements in the novel Tess of the D'Urbevilles by Thomas Hardy. The characteristics of the characters, the social context, and the ancient, traditional religion will all be examined in this paper's analysis of Tess of the d'Urbervilles. The article explains the factors that led to Tess's tragic destiny, including the main characters' contradictory morals, unfair laws, and the downturn of capitalism. This research is qualitative in nature. Tess of the D'Urbervilles is a tragedy about life and love at the same time. The process of conflict between the protagonists and the societal setting is what defines a tragedy. Either the character acting as the primary factor, the environment acting as the primary guide, or the outcome of the interaction between the two, is the cause of the tragedy. Tess is merely one of the victims going through hardships. Tess allows us to observe women's inferior status simultaneously, demonstrating the need for us to cultivate a revolting attitude and a habit of economic independence.